Skrining dan Edukasi Pencegahan Frambusia Puskesmas Kupu di SDN 01 Lawatan Kabupaten Tegal - Destra, Edwin; Anggraeni, Natasha; Prakoso, Ariel Bagoes; Ashil , Rafidah Hanina; Jamaludin , Jamaludin; Juliastina , Mika Jaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Frambusia, also known as yaws, patek, pian, buba, or ambalo, is a tropical disease categorized as a Neglected Tropical Disease (NTD). The diagnosis of frambusia is established through clinical examination and serological testing. Occasionally, there are cases of frambusia that lack clear clinical lesions, leading to undiagnosed instances. The disease is primarily attributed to unhygienic living conditions, and if left untreated, it can result in various complications in the future. TPHA-RDT testing can be employed for early frambusia detection. Educational activities and disease screening involve 12 pediatric respondents. Frambusia is commonly observed among children aged two to fifteen years, with transmission occurring during play and interaction with peers of the same age group. Therefore, effective preventive measures, such as frambusia screening, need to be implemented. Societal awareness campaigns contribute to enhancing public knowledge of frambusia and educating individuals about effective preventive actions. With an improved understanding of this disease, it is expected that individuals will take necessary preventive steps, such as seeking healthcare when frambusia symptoms or signs arise. Thus, accurate knowledge of frambusia serves as a foundation for adopting effective preventive behaviors and safeguarding the overall health of both individuals and communities.